The effect of academic supervision and work motivation on the performance of elementary school teachers in Kempas district, Indragiri Hilir regency - Abu Nawas; Isjoni; Elfis Suanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This study aims to analyze the significant and positive influence of (a) academic supervision on teacher performance, (b) teacher work motivation on teacher performance, and (c) both academic supervision and work motivation on the performance of elementary school teachers in Kempas District, Indragiri Hilir Regency. This research employs a descriptive quantitative method with a correlational research technique (ex post facto). The population comprises 156 elementary school teachers, with a randomly selected sample of 113 respondents. A questionnaire was used as the research instrument, and a trial was conducted with 30 respondents outside the main sample. Data analysis was performed using descriptive and inferential statistics. The findings indicate that academic supervision positively and significantly influences teacher performance, with a significance value of 0.000 < 0.05 and a contribution of 80.8%. Similarly, work motivation has a positive and significant impact on teacher performance, with a significance value of 0.000 < 0.05 and a contribution of 82.7%. Furthermore, academic supervision and work motivation have a positive and significant effect on teacher performance, with a significance value of 0.000 < 0.05 and a combined contribution of 88.1%. In conclusion, academic supervision and work motivation are crucial factors in enhancing teacher performance.